2008
DOI: 10.1002/rsa.20209
|View full text |Cite
|
Sign up to set email alerts
|

What is the furthest graph from a hereditary property?

Abstract: For a graph property P, the edit distance of a graph G from P, denoted E P (G), is the minimum number of edge modifications (additions or deletions) one needs to apply to G in order to turn it into a graph satisfying P. What is the furthest graph on n vertices from P and what is the largest possible edit distance from P? Denote this maximal distance by ed(n, P). This question is motivated by algorithmic edge-modification problems, in which one wishes to find or approximate the value of E P (G) given an input g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(85 citation statements)
references
References 22 publications
(34 reference statements)
3
82
0
Order By: Relevance
“…[4], [5], [9], [13], [18], [19]). It was shown that various classical extremal results for monotone graph properties have a natural analogue for some hereditary properties.…”
Section: Definitions and Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…[4], [5], [9], [13], [18], [19]). It was shown that various classical extremal results for monotone graph properties have a natural analogue for some hereditary properties.…”
Section: Definitions and Backgroundmentioning
confidence: 99%
“…The usage of these definitions is to model regular partitions of graphs. This is done via Lemma 3.4 which is proved in [4]. This powerful lemma allows us to omit some of the tedious details that usually accompany the usage of the regularity lemma.…”
Section: Partitions and Colored Regularity Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of the edit distance in graphs was originated independently by Axenovich, Kézdy and Martin [4] and Alon and Stav [3]. Since then, there has been a great deal of study on the edit distance itself and on the so-called edit distance function (see for example [1], [5]).…”
Section: Introductionmentioning
confidence: 99%